2001
DOI: 10.1093/intimm/13.9.1203
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct steps of immigration of hematopoietic progenitors into the early thymus anlage

Abstract: Thymic epithelial cells, which create a three-dimensionally organized meshwork structure peculiar to the thymus, develop from simple epithelia of the third pharyngeal pouch and cleft during organogenesis. We comparatively investigated the thymus anlages of normal and nude mice by immunohistochemical analysis with regard to epithelial organization and distribution of hematopoietic progenitor cells at early stages of organogenesis. Our results show that development of the mouse thymus anlage at early stages can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 40 publications
6
101
1
4
Order By: Relevance
“…In E11.5 wild-type mice, many hematopoietic progenitors that express IKAROS protein were located in the outer mesenchymal layer of the thymus anlage and lined the border of the epithelial anlage ( Fig. 1A) (27). The numbers of these cells in E11.5 CXCL12 Ϫ/Ϫ mice on a C57BL/6 background were comparable to those seen in wild-type mice (Fig.…”
Section: Impaired Expansion Of T Cell Precursors In the Thymus From Cmentioning
confidence: 62%
“…In E11.5 wild-type mice, many hematopoietic progenitors that express IKAROS protein were located in the outer mesenchymal layer of the thymus anlage and lined the border of the epithelial anlage ( Fig. 1A) (27). The numbers of these cells in E11.5 CXCL12 Ϫ/Ϫ mice on a C57BL/6 background were comparable to those seen in wild-type mice (Fig.…”
Section: Impaired Expansion Of T Cell Precursors In the Thymus From Cmentioning
confidence: 62%
“…The migration of hematopoietic progenitors into the thymic primordium is initiated between E11 and E12, which corresponds temporally to the appearance of K8 ϩ K5 ϩ TEC clusters (20,21). This correlation suggests that interactions with differentiating thymocytes might induce K5 up-regulation in fetal TECs.…”
Section: Resultsmentioning
confidence: 92%
“…Itoi et al (20) reported that the thymic epithelium converts from a stratified bilayered epithelium at E11 to a clustered organization by E12 and a meshwork structure by E13. Our findings are consistent with this report and further show that K5 is up-regulated in a subset of TECs concomitant with or shortly after the thymic epithelium assumes a three-dimensional structure.…”
Section: It Is Not Yet Clear Whether the K8mentioning
confidence: 99%
“…Upon challenges, upregulation of Foxn1 was a common feature of thymus regeneration, but the timing of Foxn1 expression changed and the responding TEC subsets depended on the type of treatment. Whereas dexamethasone and recombinant human fibroblast growth factor 7 …”
mentioning
confidence: 99%
“…Separation of the common anlage coincides with the arrival of hematopoietic precursor cells from the bone marrow inside the thymus at embryonic day (E)12 (6,7). Although Foxn1-deficient mutants lack a functional thymus, a Foxn1-deficient thymic anlage nevertheless forms and migrates to its final mediastinal position above the heart (8).…”
mentioning
confidence: 99%